2015
DOI: 10.3126/ijasbt.v3i1.12063
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxicity of Profenofos 50% EC (curacron 50 EC) to Vigna radiata,L. seedlings: II. Studies on Biochemical Parameters

Abstract: Profenofos 50% EC (curacron 50 EC) is a hazardous pesticide commonly used in agriculture is also an important contaminant of environment.Its presence in biological system has gained importance due to bioaccumulation in food chain. The phyto-toxic effect of profenofos wasassessed based on the biochemical parameters (Shoot and Root) of seedlings (Amino acids, Protein, Sugar, DNA and RNA) of the test species,Vigna radiata,L. The concentrations of pesticide chosen were based on EC50 and are in the range of 0.02, 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Although the treatment with the chemical product was effective in controlling D. dipsaci, the yield of the treated plants was similar to that of the absolute control, which suggests a phytotoxic effect of Cypermectrin and/or Profenofos, which has been reported in the past and related to the alteration of cell division processes, synthesis of amino acids and nucleic acids, as well as the reduction of the contents of photosynthetic pigments (chlorophyll) in plants [57] [58] [59] [60].…”
Section: Discussionmentioning
confidence: 57%
“…Although the treatment with the chemical product was effective in controlling D. dipsaci, the yield of the treated plants was similar to that of the absolute control, which suggests a phytotoxic effect of Cypermectrin and/or Profenofos, which has been reported in the past and related to the alteration of cell division processes, synthesis of amino acids and nucleic acids, as well as the reduction of the contents of photosynthetic pigments (chlorophyll) in plants [57] [58] [59] [60].…”
Section: Discussionmentioning
confidence: 57%
“…Analysis and ANOVA indicates the statistical highly significance and the change in peroxidase activity in leaves were the tested compounds treatment dependent. The results were obtained by Chauhan et al (2013), Mishra et al (2015) and Ashrafi and Pandit (2016) who showed that the imidacloprid and profenophos treatments increased enzyme (catalase, peroxidase and polyphenol oxidase) activity. Homayoonzadeh et al (2020) studied imidacloprid and dichlorvos sprayed to control cucumber whiteflies on cucumber seedlings.…”
Section: Effect Of Tested Pesticides On Antioxidant Enzymesmentioning
confidence: 78%
“…This higher toxicity of ATR was already explained in terms of its molecular structure. The latter is specifically tailored for ATR to act as an herbicide unlike diazinon that rather exhibits insecticide features [ 28 , 29 , 30 , 31 ]. This EC50 value of ATR is slightly lower than that reported for L. minor but approximately twice lower as compared to that registered for other living species such as L. gibba (0.089 mg L −1 ) [ 25 , 32 , 33 , 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%